2015
DOI: 10.1371/journal.pone.0117139
|View full text |Cite
|
Sign up to set email alerts
|

Unique Expression Pattern and Functional Role of Periostin in Human Limbal Stem Cells

Abstract: Periostin is a non-structural matricellular protein. Little is known about periostin in human limbal stem cells (LSCs). This study was to explore the unique expression pattern and functional role of periostin in maintaining the properties of human LSCs. Fresh donor corneal tissues were used to make cryosections for evaluation of periostin expression on ex vivo tissues. Primary human limbal epithelial cells (HLECs) were generated from limbal explant culture. In vitro culture models for proliferation and epithel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 49 publications
1
6
1
Order By: Relevance
“…The apparent discrepancy between site of POSTN mRNA expression and protein deposition indicates that corneal surrounding tissues are responsible for active POSTN expression, which then translocates to the corneal periphery. This is supported by a previous study showing that human POSTN is expressed by limbal stem cells which differentiate into the corneal epithelium .…”
Section: Resultssupporting
confidence: 85%
“…The apparent discrepancy between site of POSTN mRNA expression and protein deposition indicates that corneal surrounding tissues are responsible for active POSTN expression, which then translocates to the corneal periphery. This is supported by a previous study showing that human POSTN is expressed by limbal stem cells which differentiate into the corneal epithelium .…”
Section: Resultssupporting
confidence: 85%
“…This is in good agreement with the expected molecular mass of this protein (93.3 kDa), 3 and was similar to that found in other human epithelial tissues like the cornea. 20 The small differences between our results and others could be related to occurrence of tissue specific periostin isoforms, or post-translational processes of the protein. Based on image densitometry the relative level of periostin varies among different segments of the gingiva.…”
Section: Discussioncontrasting
confidence: 82%
“…Nevertheless, other studies on epithelial tissues reported the presence of periostin immunoreactivity in the basal keratinocytes, basal lamina, and dermal fibroblasts in healthy human skin, 21 , 22 or in the basal layer cells of the human corneal epithelium. 20 According to those authors periostin only becomes extracellular during tissue remodeling of wound repair. 21 , 22 Since in normal gingiva periostin is exclusively extracellular, its function may be distinct from that of skin, 17 and the presence of intracellular periostin probably reflects non-secreted protein.…”
Section: Discussionmentioning
confidence: 99%
“…POSTN also induces proliferation and regeneration of human limbal stem cells with accompanied activation of integrin β1 and TCF4 19 . AKT/GSK-3β/β-catenin pathway has been well studied in cancer stem cell and β-catenin/TCF4/Nanog also has been reported to drive a progenitor-like cell phenotype of tumor cells 20, 21 .…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that stromal derived POSTN promotes cancer progression including maintaining the phenotype of cancer stem cell via Akt, Wnt/β-catenin signaling pathway through binding to integrin receptors 18 . POSTN also induces proliferation and regeneration of human limbal stem cells with accompanied activation of integrin β1 and TCF4 19 . AKT/GSK-3β/β-catenin pathway has been well studied in cancer stem cell and β-catenin/TCF4/Nanog also has been reported to drive a progenitor-like cell phenotype of tumor cells 20 , 21 .…”
Section: Resultsmentioning
confidence: 99%